Reaching Movement Onset- and End-Related Characteristics of EEG Spectral Power Modulations - Demandt, Evariste; Mehring, Carsten; Vogt, Klaus; Schulze-Bonhage, Andreas; Aertsen, Ad; Ball, Tonio (Frontiers in Neuroscience, 2012)
The spectral power of intracranial field potentials shows movement-related modulations during reaching movements to different target positions that in frequencies up to the high-γ range (approximately 50 to above 200 Hz) can be reliably used for single-trial inference of movement parameters. However, identifying spectral power modulations suitable for single-trial analysis for non-invasive approaches remains a challenge. We recorded non-invasive electroencephalography (EEG) during a self-paced center-out and center-in arm movement task, resulting in 8 reaching movement classes (4 center-out, 4 center-in). We found distinct slow (≤ 5 Hz), μ (7.5 to 10 Hz), β (12.5 to 25 Hz), low-γ (27.5 to approximately 50Hz) and high-γ (above 50 Hz) movement onset- and end-related responses. Movement class-specific spectral power modulations were restricted to the β band at approximately 1 s after movement end and could be explained by the sensitivity of this response to different static, post-movement electromyography (EMG) levels. Based on the β band, significant single-trial inference of reaching movement endpoints was possible. The findings of the present study support the idea that single-trial decoding of different reaching movements from non-invasive EEG spectral power modulations is possible, but also suggest that the informative time window is after movement end and that the informative frequency range is restricted to the β band.